Vórtice ciclônico em altos níveis associado à corrente de jato no nordeste brasileiro nos anos de 1998-2007 - Costa, Micejane da Silva (2010)
Connection between upper tropospheric cyclonic vortex (UTCV) and jet stream in the Northeastern region of Brazil (JSNEB) were analyzed for 10 years (1998-2007). These studies are necessary for short term weather forecasting improvement in the Alagoas State of Brazil. The National Centers for Environmental Prediction/ National Center for Atmospheric Research (NCEP/NCAR) reanalysis data were used for elaborate 200 hPa streamlines fields at 00:00 UTC. The 3.652 streamlines fields were analyzed. All events of UTCV with and without JSNEB were identified. During study period 214 UTCVs near NEB were observed and 147 of them above the Alagoas State. 63% UTCV events near Alagoas were associated with JSNEB. The durations of UTCVs and UTCV with JSNEB were on an average 3.8 and 3.0 days, respectively. The UTCVs were observed throughout the year, excluding July. UTCV with JSNEB were registered throughout the year except July and September and were stronger in the warm period (November - March). All JSNEB were weak, wind velocity at the nucleus center was at an average 32(verificar valor) ms-1 and value maximum reached 44m/s. The predominant velocity was 20-28ms-1 and was registered in 78% of events. The CJNEB direction from South, West, Nortwest and Southeast were observed more frequently. Three circulation pattern Zonal, Meridional and Transversal were obtained. For example, each circulation pattern was described in details. The precipitation in Alagoas State, associated with the Zonal, Meridional and Transversal events, were studied.